Periparturient disorders in dairy cows - Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
The economic climate in the dairy industry requires producers to operate efficiently to remain competitive. Attention to details and understanding of reproduction, metabolism, digestive functions, milk secretion, and all aspects of husbandry are essential. To be successful, producers must minimize reproductive failure because reproductive performance affects the quantity of milk produced per cow per day of herd life, the number of potential replacements needed to maintain a constant herd size, and the longevity of the cow in the herd. In practice, this translates into well-designed programs of herd health, milking, feeding, and reproductive management that minimize involuntary culling of. problem cows by maintaining healthy, profitable cows. The purpose of this review is to focus on the interrrelationships of various periparturient disorders in dairy cows and highlight their collective impact on reproductive performance, milk yield, and predisposition to other diseases.
Keywords: Dairy; Periparturient; Reproductive; Milk